Konstruksi Makna Kolektor Photocard (Studi Fenomenologi Mengenai Makna, Motif, dan Pengalaman Komunikasi Kolektor Photocard K-Pop) - Maisarah, Fauziah; Abidin, Zainal; Teguh, Made Panji (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
K-Pop photocards, which are part of K-Pop merchandise packages, have a lot of devotees, so it's not uncommon for photocards to have high selling prices. Photocards are so popular among K-Pop fans that many deliberately collect K-Pop photocards. They do not hesitate to spend money to buy. K-Pop photocard collectors also often receive negative comments from other people because they like to collect K-Pop photocards. This study uses a qualitative method with a phenomenological approach, with the aim of finding meaning, motives, and communication experiences of K-Pop photocard collectors, this study uses Alferd Schutz phenomenological theory and Erving Goffman self-presentation theory. The informants in this study were 3 K-Pop photocard collectors. To get the meaning, motives, and experiences of K-Pop photocard collectors, researchers must research in depth so that informants provide true information. The results of the study show that informants have various meanings in collecting K-Pop photocards, namely as happiness, wealth, and killing time. As for the motives that prompted the informants to collect K-Pop photocards, there were several because motives (motif kerena), namely because of aesthetics, benefits, and dissatisfaction. Meanwhile, in order to motives (motif untuk) were found to be related to 3 things, namely happiness, finance and perfection. Communication experiences also varied, namely communication experiences obtained from parents, friends, and K-Pop Photocard sellers in the form of positive and negative communication experiences. Keywords: Phenomenology, Self-presentation, Meaning, Motives, Communication Experience, Photocard K-Pop